New Insights Into Interactions of Presynaptic Calcium Channel Subtypes and SNARE Proteins in Neurotransmitter Release - Rongfang He; Rongfang He; Juan Zhang; Yiyan Yu; Laluo Jizi; Weizhong Wang; Miaoling Li (Frontiers in Molecular Neuroscience, 2018)
Action potential (AP) induces presynaptic membrane depolarization and subsequent opening of Ca2+ channels, and then triggers neurotransmitter release at the active zone of presynaptic terminal. Presynaptic Ca2+ channels and SNARE proteins (SNAREs) interactions form a large signal transfer complex, which are core components for exocytosis. Ca2+ channels serve to regulate the activity of Ca2+ channels through direct binding and indirect activation of active zone proteins and SNAREs. The activation of Ca2+ channels promotes synaptic vesicle recruitment, docking, priming, fusion and neurotransmission release. Intracellular calcium increase is a key step for the initiation of vesicle fusion. Various voltage-gated calcium channel (VGCC) subtypes exert different physiological functions. Until now, it has not been clear how different subtypes of calcium channels integrally regulate the release of neurotransmitters within 200 μs of the AP arriving at the active zone of synaptic terminal. In this mini review, we provide a brief overview of the structure and physiological function of Ca2+ channel subtypes, interactions of Ca2+ channels and SNAREs in neurotransmitter release, and dynamic fine-tune Ca2+ channel activities by G proteins (Gβγ), multiple protein kinases and Ca2+ sensor (CaS) proteins.